2010
DOI: 10.1200/jco.2010.30.0731
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Introducing Stereotactic Lung Radiotherapy for Elderly Patients With Stage I Non–Small-Cell Lung Cancer: A Population-Based Time-Trend Analysis

Abstract: SBRT introduction was associated with a 16% absolute increase in RT use, a decline in the proportion of untreated elderly patients, and an improvement in OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
263
3
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(284 citation statements)
references
References 40 publications
8
263
3
10
Order By: Relevance
“…In clinical practice, a multidisciplinaryapproach could probably be of great value in determining the besttreatment strategy in every single patient, taking into accountclinical factors like respiratory function, tumor's stage, age andcomorbidities, and offering the proper choice in terms of efficacyand morbidity [21,22]. In the study by Palma et al [12], on elderlypatients with a median age of 79 years old, SABR had a 30-day mor-tality rate of <2%; this result can be of particular importance fordecision making, as patients are obviously reluctant to accept risksthat involve the possibility of short-term death. A Markov-modelbased comparison of surgery versus SABR for patients aged 65 or older predicted that surgery might confer an overall survival bene-fit of 2-3% at 5 years over SABR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, a multidisciplinaryapproach could probably be of great value in determining the besttreatment strategy in every single patient, taking into accountclinical factors like respiratory function, tumor's stage, age andcomorbidities, and offering the proper choice in terms of efficacyand morbidity [21,22]. In the study by Palma et al [12], on elderlypatients with a median age of 79 years old, SABR had a 30-day mor-tality rate of <2%; this result can be of particular importance fordecision making, as patients are obviously reluctant to accept risksthat involve the possibility of short-term death. A Markov-modelbased comparison of surgery versus SABR for patients aged 65 or older predicted that surgery might confer an overall survival bene-fit of 2-3% at 5 years over SABR.…”
Section: Discussionmentioning
confidence: 99%
“…The routine use of SABR outside clinical trials has continuously increased overthe last years in most countries: a US survey reported that 57% ofresponding physicians practiced SBRT for lung cancer in 2010 [10],and an Italian survey showed that SABR was used in 41% of depart-ments [11]. Palma et al [12] analyzed the time trend in SABR use inelderly patients in the Netherlands, showing an incessant increasein indications in patients previously either untreated or addressedto palliative RT. In this frame, few data are available on efficacyand toxicity of SABR outside clinical trials, especially in patientswith histological diagnosis, a subgroup whose disease characteris-tics can be considered analogous to the surgical population (exceptfor the difference in associated comorbidities).Aim of the present retrospective observational study on a Ital-ian multicenter cohort was to provide further data on outcomes andprognostic factors in a quite large group of patients affected withstage I histologically confirmed NSCLC; the analysis was focused onthe possible impact of multiple variables and on either the confir-mation of known prognostic factors or the selection of new ones,if any.…”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic ablative body radiotherapy (SABR) has been developed as a treatment option for early NSCLC and is providing proof of principle evidence for accelerated dose escalation. Over the past 5 years the published evidence for SABR has increased 19,20 and consistently shows impressive local control rates of around 90% at 5 years, with evidence that this contributes to improved outcomes across a population 21 . However, there is little published randomised trial data comparing SABR with 'conventionally' fractionated radiotherapy, and the data presented has yet to show superior outcomes with SABR 22 .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The Radiation Therapy Oncology Group trial 0236 has reported a survival rate of 55.8% at 3 years, with high rates of local tumour control (90.6%) and moderate treatment-related morbidity. 7 Although no Phase III trials have been published comparing surgery with SBRT, the introduction of SBRT has improved the survival of patients with medically inoperable Stage I NSCLC in a population-based analysis in the Netherlands 8 and could be an option in patients who are operable, according to the results of a pooled analysis of two randomized trials [stereotactic ablative radiotherapy in stage 1 non-small-cell lung cancer patients who can undergo lobectomy (STARS) and radiosurgery or surgery for operable early stage non-small-cell lung cancer (ROSEL)]. 9 However, studies of current patterns of practice for NSCLC on 424 American Society for Radiation Oncology (ASTRO)-affiliated radiation oncologists in the USA found that only a minority of physicians have employed SBRT to treat patients with Stage I NSCLC.…”
Section: Introductionmentioning
confidence: 99%